INTERVENSI RELIGIOUS-REBT MELALUI LAYANAN KONSELING INDIVIDU DALAM MENGATASI SOSIO-EMOSIONAL ANAK BINAAN DI LPKA KELAS I TANGERANG - Azahra, Tiara; Handoyo, Alfiiandy Warih; Prabowo, Arga Satrio (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Adolescence is a transitional period toward adulthood that is vulnerable to influence, marked by physical, cognitive, and socio-emotional changes. Parents and families play an important role in shaping the values, norms, and behaviors of adolescents. Healthy families help build self-confidence, emotional management skills, and adaptive behaviors. Conversely, dysfunctional families can trigger emotional instability and increase the risk of deviant behavior. The Tangerang Class I LPKA is a rehabilitation center for adolescents in conflict with the law. They are rehabilitated through training, skills development, and education to prepare them for reintegration into society. However, the length of the rehabilitation period with repetitive activities and minimal exposure to the outside world affects the socio-emotional condition of the children at the LPKA. Family support is essential in maintaining mental health, but access to communication is often limited due to the distance between their homes and Banten. This is where guidance and counseling, especially individual counseling, plays a role as a forum for the children to express their thoughts and feelings. Positive emotional encouragement enables them to find a deeper meaning in life. Through the Religious-Rational Emotive Behavior Therapy approach, it helps reduce irrational thinking patterns that influence how individuals control their emotions and behavior. A spiritual approach is also important in helping foster children find meaning in life, inner peace, and realize the value and morality in their actions and decisions.